Priority degrees for hesitant fuzzy sets: Application to multiple attribute decision making - Jibin Lan; Ruifang Jin; Zhaoyi Zheng; Mingming Hu (Operations Research Perspectives, 2017)
In this paper, some drawbacks to existing ordering relations for hesitant fuzzy sets are examined using examples. To overcome these flaws, a priority degree formula for comparing two hesitant fuzzy sets is presented and the desirable priority degree properties studied. Then, based on an introduced priority degree formula, a new hesitant fuzzy multiple attribute decision making methodology is proposed. Finally, a numerical example together with a comparison analysis is given to illustrate the effectiveness and feasibility of the new approach to decision making applications.
Keywords: 330; Priority degree; Order relations; Hesitant fuzzy sets; Multiple attribute decision making